2016
DOI: 10.3389/fpls.2016.00999
|View full text |Cite
|
Sign up to set email alerts
|

Micrasterias as a Model System in Plant Cell Biology

Abstract: The unicellular freshwater alga Micrasterias denticulata is an exceptional organism due to its complex star-shaped, highly symmetric morphology and has thus attracted the interest of researchers for many decades. As a member of the Streptophyta, Micrasterias is not only genetically closely related to higher land plants but shares common features with them in many physiological and cell biological aspects. These facts, together with its considerable cell size of about 200 μm, its modest cultivation conditions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 168 publications
(259 reference statements)
1
49
0
Order By: Relevance
“…The desmids (Desmidiales, Zygnematophyceae) have been established as a model group for investigation of morphological symmetry at the cellular level [11, 12]. They have also been a prime model system for the study of the intracellular mechanisms of plant cell morphogenesis [1316] and mathematical modelling of the cellular growth and development [17–19]. The cellular shapes of many desmids typically have extremely low isoperimetric quotients, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The desmids (Desmidiales, Zygnematophyceae) have been established as a model group for investigation of morphological symmetry at the cellular level [11, 12]. They have also been a prime model system for the study of the intracellular mechanisms of plant cell morphogenesis [1316] and mathematical modelling of the cellular growth and development [17–19]. The cellular shapes of many desmids typically have extremely low isoperimetric quotients, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that vesicular transport during semicells morphogenesis is regulated by MdRABE1, a protein belonging to the Rab family, which may have a potential role in signalling processes associated with cell shape formation [37]. Pattern formation at actively growing areas is also accompanied by a local influx of Ca 2+ ions [14, 16, 38]. During morphogenesis, this calcium influx tightly reflects the branching pattern of the developing lobes and lobules [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They produce complex sugars and polysaccharides (Dupree and Sherrier, 1998;Goubet et al, 2009) that may explain the resistant property of the vesicle wall. Cell wall secretion is mediated by GA in chlorophyte Micrasterias (Meindl, 1993;Lütz-Meindl and Broch-Salomon, 2000) resulting in an ornamented cell shape, and in the formation of retaining wall conjoining the cells of colonial Botryococcus braunii (Weiss et al, 2012).…”
Section: Intracellular Complexity and Innovation Of The Secondary Wallmentioning
confidence: 99%